Failure by Design: The California Energy Crisis and the Limits of Market Planning - Georg Rilinger (University of Chicago Press, 2024)
A new framework for studying markets as the product of organizational planning and understanding the practical limits of market design. The Western energy crisis was one of the great financial disasters of the past century. The crisis began in April 2000, when price spikes started to rattle California's electricity markets. Decades later, some blame economic fundamentals and ignorant politicians, while others accuse the energy sellers who raided the markets. In Failure by Design, sociologist Georg Rilinger offers a different explanation, one that focuses on the practical challenges of market design. The unique physical attributes of electricity made it exceedingly difficult to introduce markets into the coordination of the electricity system, so market designers were brought in to construct the infrastructures that coordinate how market participants interact. An exercise in social engineering, these infrastructures were intended to guide market actors toward behavior that would produce optimal market results and facilitate grid management. Yet, though these experts spent their days worrying about incentive misalignment and market manipulation, they unintentionally created a system riddled with opportunities for destructive behavior. Rilinger's analysis not only illuminates the California energy crisis but also develops a broader theoretical framework for thinking about markets as the products of organizational planning and the limits of social engineering, contributing broadly to sociological and economic thinking about the nature of markets.
Keywords: 300; California energy crisis; economic sociology; social engineering; algorithmic management; economics; work and technology; market failure; social planning; market design; platform economy; electricity markets